2019
DOI: 10.1002/ejoc.201801609
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Based Cyclodextrins for the Development of New Hydrosoluble Amphiphilic Compounds

Abstract: A new family of amphiphilic cyclodextrins produced from oleic acid derivatives and maleic anhydride is described. These amphiphilic cyclodextrins are synthesized in two steps. The first step is the alkenylation of maleic anhydride by oleic acid derivatives to produce the oleic succinic anhydrides. The second step is the grafting of the oleic succinic anhydrides on various cyclodextrins. A self‐inclusion of the alkyl chain or an inclusion of one alkyl chain in the cavity of another CD is showed by NMR experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This result confirmed that a rhodium catalyst was necessary to produce the cyclic anhydrides. For comparison, the entries 5 and 6 recalled our already published branched anhydrides obtained by thermic way . The two results showed that higher temperature (220 °C vs. 140 °C) was necessary to produce a higher quantity of branched products in a shorter time.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This result confirmed that a rhodium catalyst was necessary to produce the cyclic anhydrides. For comparison, the entries 5 and 6 recalled our already published branched anhydrides obtained by thermic way . The two results showed that higher temperature (220 °C vs. 140 °C) was necessary to produce a higher quantity of branched products in a shorter time.…”
Section: Resultsmentioning
confidence: 91%
“…The second step of the synthetic pathway is the grafting of the unsaturated or saturated BSA/CSA mixture on β‐CD. This step was performed as described for the syntheses of amphiphilic β‐CD esters of alkenyl succinic acids published mainly by the group of de Rossi and others groups , . The reaction was done in pyridine with 2 molar equivalents of the anhydride functions of the BSA/CSA mixture with respect to β‐CD and allowed to produce various oleic succinyl‐β‐CDs (Scheme and Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OS-CDs synthesis was conducted in two steps as previously reported by our group [31,32]. The first step involved the alkenylation of maleic anhydride by methyl oleate and oleic acid, leading to the formation of maleinised methyl oleate or maleinised oleic acid, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenation of 2-methylbut-3-en-2-ol gave the corresponding saturated alcohol with full conversion and 100 % selectivity with stable activity in three runs ( Recently, the synthesis of new amphiphilic oleic acid based cyclodextrin materials was reported by reacting CDs with oleic succinic anhydride. [41] These amphiphilic preparations are highly water-soluble and have low surface tension and low criticalaggregation concentration. Of these products, 15-βCD with a substitution degree of 1.6 was used to stabilize ruthenium nanoparticles (2.56 � 0.60 nm) by reducing Ru(NO)(NO 3 ) 3 and 15-βCD (1 : 3 ratio) with NaBH 4 and applying the resulting catalyst in hydrogenations.…”
Section: Hydrogenation Of Other Compoundsmentioning
confidence: 99%